Exemplary Values of Social Studies Learning in Elementary School - Azizah, Nur; Mira; Delima, Rika; Sabilah, Adina; Karmelia, Mila; Sopiah; Safrudin (Universitas Pendidikan Ganesha, 2022)
So far, most of the social studies education learning process at the school level is still conventional. It is undeniable that nowadays, many symptoms and social problems continue to be turbulent and disturb the life of society, nation, and state. The current state of social studies learning, especially at the elementary level, indicates neglect of local culture, which functions to build student character. It is due to the low exemplary and moral values of a student. This study aims to This study aims to analyze the values of exemplary social studies learning in elementary schools. This type of research is qualitative approach research chosen in this study to answer the questions. Data collection in this study is by interview and documentation. The method used in this study is a method with qualitative data collection. The data analysis technique used qualitative analysis. The results showed that exemplary values in social studies learning affected elementary school students. The implications of this research are expected to be able to instill exemplary values in social studies learning in elementary schools.